Method development for forensic analysis of body odour using gas chromatography-mass spectrometry - a/p Rajan, Revathi (2015)
Body odour of an individual has unique composition due to the influence of specific combination of genetic, diet and environment on the production of the compounds responsible for giving this odour. The characteristic of human odour could be used as a human chemical fingerprint for forensic identification purposes. This research focused on developing an easy, fast and reliable method to collect, prepare and analyse the components of human body odour. The odour was collected from male subjects using a pre-treated gauze material. The subject was requested to exercise for 30 minutes prior to sampling by using the gauze to wipe over the right arm before sealing the gauze in a 5 mL eppendorf tube. Before sealing dihexyl ketone (internal standard), anhydrous sodium sulphate and also 1 mL methanol were added into the tube and left overnight at room temperature. The gas chromatography-mass spectrometer was used for the detection and identification of the components of human body odour. Two different injection systems; direct static headspace injection without pre-concentration and also the liquid injection system were compared for their suitability for this analysis. Sample preparation techniques for liquid injection by steam distillation followed by liquid-liquid extraction as well as direct extraction method using several different solvents were compared for the effectiveness to extract analyte from the collection material. This study demonstrated that direct extraction method using methanol as extraction solvent and analysis through liquid injection system via GC-MS were the optimum analysis method for body odour. Qualitative method validation was performed to evaluate the selectivity, specificity, sensitivity, linearity and stability of this method. The evaluated parameters validated the method fitness for its purpose. The analysis of the body odour revealed that it contains majority of organic acids with thirteen carbons and above, alkanes, alkenes, alcohol and others. Analysis of the compounds in the odour of the subjects by applying the developed method reveals that primary odour components can be used to identify an individual. In addition, the compounds present in the sweat of an individual are also useful to identify specific habit of a person, for example; smoking, medications consumed, and drug abuse. In conclusion, chemical fingerprint of body odour may be used to aid forensic investigation to identify and also narrow down suspect pool.